PENGELOLAAN SURAT DINAS DAN ARSIP BAGI KEPALA SEKOLAH DAN TENAGA ADMINISTRASI SEKOLAH DASAR DI KECAMATAN JATINEGARA KOTA ADMINISTRASI JAKARTA TIMUR - Neti Karnati; Unifah Rosyidi; Wahyu Sri Ambar Arum (Program Studi Manajemen Pendidikan, 2020)
Elementary school administration is an activity to support the success of thequality of education in elementary schools. The scope of school administration activitiesincludes the management of official letters and school archives. Management of officialletters and archives in primary schools is carried out by the principal, assisted by a schooloperator. Their ability to manage official documents and school archives is still lacking.Efforts to increase the capacity of school principals and elementary school administrativepersonnel can be provided with training on managing official letters and school archives.The object (target audience) of the training activities is 150 people consisting of 2elementary school supervisors, 58 school principals, 83 school administration staff and 7SDN teachers in Jatinegara sub-district. The partners involved are the Regional EducationOffice of East Jakarta Administrative City. The training has been carried out for a day onThursday, October 8, 2020 through virtual zoom cloud metting. The training materialconsists of: school leadership and administration, management of official letters andmanagement of school records. The three materials were delivered by 3 lecturers of the UNJFIP Education Management study program with the lecture, question and answer andassignment method. The results of the training were very satisfying to the participants andthe organizing committee, because all the materials had been delivered well and were veryuseful for all training participants.